PHONEME THEORY IN LINGUISTICS SCHOOLS - Usmonova, Dono Sotvoldiyevna; Usmonova, Kamola Erkinovna (INTERNATIONAL CONFERENCES, 2022)
The concept of phoneme is recognized by all linguists, but there is no uniformity in the issue of its status. At the phonological level, the generality-specificity dialectic is also reflected in the classification and analysis of phonological units. In phonological classification and analysis, phonemes are considered paradigmatically and syntagmatically.